2021
DOI: 10.1186/s41235-021-00292-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of analytical reasoning and source credibility on the evaluation of real and fake full-length news articles

Abstract: Aim Previous research has focused on accuracy associated with real and fake news presented in the form of news headlines only, which does not capture the rich context news is frequently encountered in real life. Additionally, while previous studies on evaluation of real and fake news have mostly focused on characteristics of the evaluator (i.e., analytical reasoning), characteristics of the news stimuli (i.e., news source credibility) and the interplay between the two have been largely ignored.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 49 publications
1
25
1
Order By: Relevance
“…Additionally, greater analytical reasoning was associated with this improved non-COVID fake news detection in our older adult sample. This result is consistent with previous evidence in young adults showing more accurate fake news detection with higher analytical reasoning (Bronstein et al, 2019; Pehlivanoglu et al, 2021; Pennycook & Rand, 2019, 2020; Ross et al, 2021) and extends this evidence to older adults—a population previously understudied in fake news research (see Brashier & Schacter, 2020). Importantly, findings from our direct age-group comparison suggested that news veracity detection and its association with analytical reasoning ability was similar between young and older adults.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Additionally, greater analytical reasoning was associated with this improved non-COVID fake news detection in our older adult sample. This result is consistent with previous evidence in young adults showing more accurate fake news detection with higher analytical reasoning (Bronstein et al, 2019; Pehlivanoglu et al, 2021; Pennycook & Rand, 2019, 2020; Ross et al, 2021) and extends this evidence to older adults—a population previously understudied in fake news research (see Brashier & Schacter, 2020). Importantly, findings from our direct age-group comparison suggested that news veracity detection and its association with analytical reasoning ability was similar between young and older adults.…”
Section: Discussionsupporting
confidence: 91%
“…This proposition is further supported by recent evidence that experimental enhancement of deliberative processing decreased belief in false news (Bago et al, 2020). Training interventions could entail fact-checking strategies and “nudging” to attend to diagnostic features (e.g., news source and content credibility; Pehlivanoglu et al, 2021) and/or to consider news veracity (Pennycook, McPhetres, et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although fake news represents an important subset of misinformation, fake news is unique in the sense that it involves “fabricated information that mimics news media content in form but […] lack(s) the news media's editorial norms and processes for ensuring the accuracy and credibility of information” (Lazer et al, 2018, p. 1094). This characteristic has led to a common confound in studies on fake-news beliefs, in that false statements are presented with a dubious news source and true statements are presented with a mainstream news source (for two notable exceptions, see Pehlivanoglu et al, 2021; Traberg & van der Linden, 2022). Although this confound may be common for real and fake news encountered in natural contexts, it creates ambiguity about whether a given finding is driven by the veracity of the statements or the trustworthiness of the source.…”
Section: The Current Researchmentioning
confidence: 99%
“…Limited analytical reasoning skills or scarce media literacy may explain challenges faced by adults when confronting fake news. Some research has reported that although dogmatic individuals and religious fundamentalists were more likely to believe fake news, these relationships were partially or wholly explained by lower levels of analytical reasoning (Pehlivanoglu, et al, 2021). They found that higher analytical thinking was linked to increased accuracy in detecting fake news, while analytical reasoning was not associated with greater accuracy in detecting genuine news.…”
Section: Baby Boomers and Digital Mediamentioning
confidence: 99%